Thyroid-Like Follicular Carcinoma of the Kidney in a Patient with Skull and Meningeal Metastasis: A Unique Case Report and Review of the Literature. Issue 15 (April 2016) - Dong, Liang; Huang, Jiayu; Huang, Luke; Shi, Oumin; Liu, Qiang; Chen, Haige; Xue, Wei; Huang, Yiran
Abstract : Abstract: Thyroid-like follicular carcinoma of the kidney (TLFCK) is an extremely rare subtype of renal cell carcinoma with close resemblance to the well-differentiated thyroid follicular neoplasms. TLFCK has not been included in the 2004 World Health Organization (WHO) classification due to the limited data available. Only 27 cases have been reported in the literature to date. Herein, we report a unique case of TLFCK that presented as a striking skull and meningeal metastasis 5 years after the initial diagnosis; this is the first case of TLFCK with such a novel metastasis pattern. A 68-year-old woman was found to have a right renal lesion using computed tomography (CT) during her regular clinical follow-up visit for bladder cancer, but she exhibited no obvious clinical symptoms. The CT scan showed a 4.4-cm diameter, slightly lobulated soft tissue mass in the right lower kidney, the pathological findings of which showed a TLFCK. Five years later, the patient had progressed to skull and meningeal metastasis. Both the renal tumor and the metastasis lesion were composed almost entirely of follicles with a dense, colloid-like material that resembled thyroid follicular carcinoma. However, no lesion was found in the thyroid gland. The neoplastic epithelial cells were strongly immunoreactive for cytokeratin 7 (and vimentin but negative for thyroid transcription factor-1 and thyroglobulin. This is the first reported case of TLFCK to consist of widespread metastases to the skull and meninges and provides evidence that this rare variant of renal cell carcinoma has uncertain malignant potential and can be more clinically aggressive than previously believed.